Comparison of In-Rumen Systems for Monitoring the Physiological State of Cattle - F. E. Vladimirov; S. O. Bazaev; A. R. Khakimov (Сельскохозяйственные машины и технологии)
This paper explores a method for the early detection of subacute rumen acidosis through continuous monitoring of rumen content acidity using wireless pH sensors. The study emphasizes the importance of reliable device operation and measurement accuracy as primary requirements for such devices. (Research purpose) This study aims to evaluate the functionality and accuracy of the eBolus (USA) and BoviSan (Russia, FSBSI FSAC VIM) sensors throughout their declared service life of 150 days. (Materials and methods) Three dairy cows with a rumen fistula were administered two boluses from each manufacturer during a period of 154 days. In order to ensure accurate measurements, the boluses were activated and calibrated prior to use. On the first day of data collection, the activated and calibrated boluses were sequentially immersed in buffer solutions with a pH of 4 and pH of 7. The buffer solutions were maintained at a controlled temperature of 39 degrees Celsius for a minimum of 2 hours. At 14-day intervals, the boluses were extracted from the rumen and subjected to retesting in buffer solutions. (Results and discussion) For BoviSan, the confidence interval for the mean difference suggests a systematic negative pH bias (– 0.33 to – 0.25). The average lifespan of the eBolus was determined to be 82 days, with a range of 28 to 126 days. In contrast, BoviSan boluses consistently recorded pH levels throughout their announced lifespan. Statistical analysis of the data revealed a 95% confidence interval for the mean pH difference of the eBolus boluses (– 0.02 to 0.19), indicating no significant bias. Conversely, the confidence interval for the mean difference in pH for BoviSan suggested a consistent negative bias (– 0.33 to – 0.25). (Conclusions) In practical applications, it is essential to ensure enhanced reliability of eBolus boluses, while prioritizing higher measurement accuracy with BoviSan boluses.